Empowering Self-Regulated Learning: A Case Study Using Edlink Application At PBA IAIBA Purwoasri Kediri - Baidowi, Khafidz (Kitaba, 2023)
This study endeavors to enhance the learning independence of PBA Institut Agama Islam Badrus Sholeh Purwoasri by utilizing the edlink and WhatsApp applications. Employing a quantitative approach, the research adopts a Quasi-Experimental Design. Data is collected through questionnaires and documentation, employing saturated sampling and heterogeneous group division. The analysis involves descriptive and inferential statistics. Findings indicate that the learning independence of PBA Institut Agama Islam Badrus Sholeh Purwoasri in online learning, utilizing the edlink application (Experiment), was initially in the low category during the pretest and progressed to the high category in the posttest. In the control class, the pretest showed a low category, and the posttest showed a medium category. The study reveals significant differences in learning independence between the experimental and control classes, highlighting the edlink application's impactful role in improving the learning independence of PBA Institut Agama Islam Badrus Sholeh Purwoasri Kediri.